-4n+7=1

Simple and best practice solution for -4n+7=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4n+7=1 equation:


Simplifying
-4n + 7 = 1

Reorder the terms:
7 + -4n = 1

Solving
7 + -4n = 1

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -4n = 1 + -7

Combine like terms: 7 + -7 = 0
0 + -4n = 1 + -7
-4n = 1 + -7

Combine like terms: 1 + -7 = -6
-4n = -6

Divide each side by '-4'.
n = 1.5

Simplifying
n = 1.5

See similar equations:

| 35=4y+y | | 3x+4(x+y)= | | 9+23= | | -3+8=5a+24 | | P/4-1=2 | | -61=8-4w+-14-w | | -2(2u-7)+3u=3+3(5u-1) | | 1/6b=9.2 | | 8p(p-10)=0 | | 5x=3x-10+2x | | 3y-6x+12=-6 | | 1/9b=9.2 | | 6=15-3c | | 1/50-1/×=1/30 | | 10v-v=36 | | 3(2+y)=5(2y+1) | | 5x(x-1)(3x+2)=0 | | 7(u-7)-3=-5(-4u+8)-4u | | x-2(7x-13)=11 | | 10-3v=5.56 | | pxq=12 | | (10q+7)(q-10)=0 | | 3x=2(x+2)+5 | | 6(3x+1)-39=3(2x-4) | | 3x+20+35=180 | | 3x+20+35=108 | | 12(3y-4)=-5(2x-8) | | 7/6÷14 | | 1+5x-6+2x=-19 | | (6q+7)(q+6)=0 | | x/5-6=x/5 | | -y=-3x |

Equations solver categories